East African odontopygid millipedes 3: Two new genera; Lamelloramusand Aquattuor proposed to contain three new species (Diplopoda; Spirostreptida; Odontopygidae) - Frederiksen, Sara B. (Zootaxa, 2013)
Two new genera and three new species in the millipede family Odontopygidae are described; Lamelloramus rhombiformis, L. triangularis and Aquattuor denticulatus. All three species are found in the East Usambara Mountains.